The Determinants of Corporate Hedging with Derivatives in UK Companies - ZHANG, CHENHAO (2017)
Abstract: This paper attempts to examine the determinants of corporate hedging with derivatives in UK companies. Based on previous evidences, this paper demonstrates several potential determinants of corporate hedging, which are: Growth opportunities, Alternatives for hedging, Firm size, Leverage, Tax and Foreign exposure. The sample contains 400 UK companies in different industries, and the data are collected from the annual reports from financial years of 2015 to 2016. By employing mean difference tests, logistic regressions and robustness checks, this paper suggests that liquidity, firm size, interest coverage and leverage are positively related to corporate hedging, while growth opportunities, dividend, profitability, debt maturity and foreign exposures are negatively related to corporate hedging with derivatives in UK companies.